University Language Instructors’ Preparedness for Technology-Mediated Instruction and Burnout During the COVID-19 Pandemic - Izquierdo, Jesús; Sandoval Caraveo, María del Carmen; De la Cruz Villegas, Verónika; Zapata Díaz, Rubén (Íkala, Revista de Lenguaje y Cultura, 2021)
This quantitative study explored the preparedness of foreign language teachers for technology-mediated instruction and the burnout conditions that characterized their transition from in-person to off-campus second/foreign language education during the covid-19 pandemic. The data were collected from 104 university instructors through a Google Forms® survey and a burnout questionnaire in a Mexican state which was severely hit by the virus in the spring of 2020. The survey elicited information about institutional conditions, teacher education and technology access and use. The burnout questionnaire explored exhaustion, depersonalization and accomplishment during off-campus technology-mediated language instruction. Both survey and questionnaire answers were subject to frequency analyses. In terms of teacher preparedness, data analyses revealed that the participants had a large number of teaching hours; they held sustained computer/Internet access but lacked technology-assisted language teaching training; thus, they independently sought out technological resources for the delivery of their lessons. With regard to burnout, data analyses indicated that many participants experienced exhaustion due to work overload, use of technology, and its proper integration in the lessons. Nonetheless, the use of technology helped them maintain interest in their learners, feel satisfaction and accomplish academic aims.